Community managed library? / Wan Fadzli Wan Haron dan Roziya Abu - Wan Haron, Wan Fadzli; Abu, Roziya (Universiti Teknologi MARA, Kedah, 2017)
Amongst the various kind of community library models that haven been developed around the world, it is said the only model that appears to offer the best prospect of sustainability, viability, and a suitable emphasis on users’ service quality and needs are the library authority-led community library; also known as `community managed library’. The term `community managed library’ emphasis on maintaining community private individual libraries that is designated for community intervention and management of different types. In theory, such arrangement exists in a very formal basis, which means a library authority should be able to include the services offered by such community [managed] libraries for such members of the community [users]. This paper will enlighten the pragmatism of the `community managed library’ notion in Malaysian setting and values. Several current Malaysian existing community managed library will be put forward as the foundation of the investigation on this `new’ community library model. The success and challenges faced by current Malaysian community library will be discussed.